Diagnostic Pitfalls in Acute Appendicitis - Besenzoni, Raúl A; Croci, Fabio; Fernández, Miguel (Cirugía del Uruguay, 1980)
Diagnostic piffalls in acute appendicitis is frequent. Its incidence in women increases by a 3 to 1 ratio.